Which are the best evidence-based therapeutic options for clozapine and ECT resistant schizophrenia? A case-report. (November 2021) - Damiano, Rodolfo Furlan; Avrichir, Belquiz S.; Melzer-Ribeiro, Débora L.; Sallet, Paulo Clemente; Elkis, Helio
Highlights: Treatment-resistant schizophrenia. Clozapine resistant schizophrenia. Suicide in schizophrenia. Abstract: This is a case description of a patient with clozapine and ECT resistance schizophrenia with several suicide attempts. We discussed evidence-based clinical decisions to deal with such conditions.